Correlation of Terrestrial Satellite Computation and Allocation of Influence in The Development of Digital Television Services in Indonesia - Rizky, Dede; Nusraningrum, Dewi; Bakhour, Alyssa Edwina Imad Khalid; Mulyatri, Egit; Dewi, Kayla Rosantya (Jurnal Ilmiah Manajemen dan Bisnis, 2024)
Analog television in Indonesia is currently being transformed into digital television. The purpose of this study was to determine the effectiveness and impact of the transformation of these changes. The total population of the study was unknown, so convenience sampling was used. The data obtained is processed descriptively. The results show that all respondents who earn below one million rupiah per month do not receive government assistance to convert their televisions into digital televisions, and respondents do not have knowledge about how to convert analog televisions into digital televisions.